The kite runner - Hosseini, Khaled (New York : Simon & Schuster Audio, 2003)
Story of the friendship between two boys growing up in Kabul during the final days of the monarchy. When Amir is forced to flee with his prominent and wealthy father for a new life in California, he leaves behind Hassan, the son of his father's servant. Amir cannot, however, leave the memory of Hassan behind him.
Unabridged.
In container (18 cm.).
Keywords: Betrayal -- Fiction; Boys -- Fiction; Male friendship -- Fiction; Social classes -- Fiction; Kabul (Afghanistan) -- Fiction; Afghanistan -- Fiction